2014
DOI: 10.1111/fme.12101
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of brown trout,Salmo trutta, populations from differently sized tributaries of Lake Mjøsa in south‐east Norway

Abstract: This study was based on genotyping eight microsatellite loci of 463 brown trout, Salmo trutta L., sampled in nine differently sized tributaries in three areas on the eastern shore of Lake Mjøsa, south-eastern Norway. The populations were genetically structured, and Mantel's test showed that genetic distance correlated positively with geographical distance. Temporal differentiation F ST over a 2-year period was estimated in five streams and was nonsignificant after Bonferroni correction. Effective population si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 55 publications
3
10
0
Order By: Relevance
“…This explains the low genetic diversity and the N e estimates that were below 25 according to SNPs. In previous studies on other focal systems, estimates of N e below 50 have often been observed, which are in line with our observations (Linlokken et al, ; Linlokken, Johansen, & Wilson, ; Sonstebo, Borgstrom, & Heun, ; Vøllestad, ) suggesting that many brown trout populations in brooks are naturally small and strongly genetically differentiated. Each of the studied wild populations appeared to be an isolated unit with very limited gene flow from the other rivers or from the hatchery‐reared fish, which is in line with their historical and present‐day connectivity.…”
Section: Discussionsupporting
confidence: 93%
“…This explains the low genetic diversity and the N e estimates that were below 25 according to SNPs. In previous studies on other focal systems, estimates of N e below 50 have often been observed, which are in line with our observations (Linlokken et al, ; Linlokken, Johansen, & Wilson, ; Sonstebo, Borgstrom, & Heun, ; Vøllestad, ) suggesting that many brown trout populations in brooks are naturally small and strongly genetically differentiated. Each of the studied wild populations appeared to be an isolated unit with very limited gene flow from the other rivers or from the hatchery‐reared fish, which is in line with their historical and present‐day connectivity.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies of brown trout have shown that populations spawning in inflowing versus outflowing streams of the same lake are often genetically and phenotypically differentiated, implying limited gene flow among them and potential local adaptation (Ferguson & Taggart, ; Jonsson et al, ; Linløkken, Johansen, & Wilson, ; Massa‐Gallucci et al, ; Palmé et al, ). In cases where no obvious physical barriers to dispersal exist, some combination of prezygotic behavioral isolating mechanisms (that reduce the likelihood of inflow‐origin fish straying into outflow streams and successfully mating there, or vice versa) and postzygotic ecological barriers (reduced fitness of hybrid offspring) may constrain effective dispersal and thus gene flow.…”
Section: Discussionmentioning
confidence: 99%
“…Brown trout from the different spawning tributaries were significantly differentiated, with clear difference between east and west populations (Skaala, 1992). Further, there seemed to be a significant isolation-by-distance pattern (Linløkken et al, 2014). Thus, brown trout seems more genetically differentiated than grayling in spawning tributaries to Lake Mjøsa.…”
Section: Genetic Structure Of Graylingmentioning
confidence: 94%
“…Genetic studies have also been conducted on brown trout spawning in several tributaries to Lake Mjøsa (Skaala, 1992;Linløkken et al, 2014). Brown trout from the different spawning tributaries were significantly differentiated, with clear difference between east and west populations (Skaala, 1992).…”
Section: Genetic Structure Of Graylingmentioning
confidence: 99%